2013
DOI: 10.1002/ijc.28607
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral COX‐2 inhibition enhances GM‐CSF immunotherapy against established mouse GL261 brain tumors

Abstract: Immunotherapy has shown effectiveness against experimental malignant brain tumors, but the clinical results have been less convincing most likely due to immunosuppression. Prostaglandin E 2 (PGE 2 ) is the key immunosuppressive product of cyclooxygenase-2 (COX-2) and increased levels of PGE 2 and COX-2 have been shown in several tumor types, including brain tumors. In the current study, we report enhanced cure rate of mice with established mouse GL261 brain tumors when immunized with granulocyte macrophage-col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…The primary tumour displayed the same staining patterns, although COX-2 was also seen on subsets of tumour cells. We have repeatedly observed distinct cellular origin of mPGES-1 and COX-2 in neuroblastoma44, experimental glioma49 and here in medulloblastoma, and demonstrated that inhibition of COX-2 has a therapeutic effect in vivo even though COX-2 and mPGES-1 are expressed in different cell types49. These data suggests that intermediate metabolites are transferred between cell types, as previously described50, and the MB-LU-181 model will be useful to study such interactions.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The primary tumour displayed the same staining patterns, although COX-2 was also seen on subsets of tumour cells. We have repeatedly observed distinct cellular origin of mPGES-1 and COX-2 in neuroblastoma44, experimental glioma49 and here in medulloblastoma, and demonstrated that inhibition of COX-2 has a therapeutic effect in vivo even though COX-2 and mPGES-1 are expressed in different cell types49. These data suggests that intermediate metabolites are transferred between cell types, as previously described50, and the MB-LU-181 model will be useful to study such interactions.…”
Section: Discussionsupporting
confidence: 63%
“…Immunofluorescent labeling of cryosections was performed as previously described49. The following primary antibodies were used: mouse anti-CD133/2 (5 μg/ml, Milteney Biotec GmbH, Bergisch Gladbach, Germany); FITC-mouse anti-GFAP (5 μg/ml), PE-mouse anti-human CD8 (diluted 1:10), PE-mouse anti-human CD15 (diluted 1:10), PE-mouse anti-human CD44 (diluted 1:10), FITC-mouse anti-human CD45 (diluted 1:10), FITC-mouse anti-human CD163 (diluted 1:10), rat anti-mouse NK-1.1.…”
Section: Methodsmentioning
confidence: 99%
“…Immunotherapy per se induces an immune response associated with elevated plasma IFNγ levels and CD4 + and CD8 + T cells systemically and intratumorally (Visse et al, 2000;Eberstal et al, 2012;Fritzell et al, 2013a, b;Eberstal et al, 2014). IFNγ is predominately produced by activated T cells and thus, intratumorally implanted MSCs are most likely exposed to significant levels of IFNγ.…”
Section: Discussionmentioning
confidence: 96%
“…Examination of genetic and epigenetic background and exploration of biomarkers defining a subset of lung cancer patients that would benefit by these combinations combined with better understanding of COX-2 biology would shed more light on how to achieve clinical improvement. Cox-2 inhibitors have been used with immunotherapeutic agents with effectiveness [73,74], however; more trials are necessary for non-small cell lung cancer.…”
Section: Resultsmentioning
confidence: 99%